The Effectiveness of Problem Solving-Based Student Worksheet to Improve Students’ Critical Thinking Skills - Rudibyani, Ratu Betta (Jurnal Pendidikan Progresif, 2020)
The Effectiveness of Problem Solving-Based Student Worksheet to Improve Students’ Critical Thinking Skills. Objectives: This research aimed to find out the effectiveness of student worksheets based on problem solving in science learning to improve students’ critical thinking skills. Methods: The research population were all tenth-grade science students in one of the Senior High Schools in South Lampung in the even semester of 2017/2018 academic year with the sample was selected using cluster random sampling. This research used d a quasi-experimental method with Pretest-Posttest Control Group Design.The effect of the worksheet was measured based on the mean value of n-Gain of the students’ critical thinking skills. The effect size effect size calculation was also applied. Findings: The result showed that the n-Gain value mean of the students’ critical thinking skills in the experimental was 0.71 and the effect size was 0.89. Conclusion: students’ worksheet based on problem solving in science learning is very effective to improve students’ critical thinking skillsKeywords: students’ worksheet, problem solving, critical thinking skill.